X-ray micro computed tomography, segmental relaxation and crystallization kinetics in interfacial stabilized co-continuous immiscible PVDF/ABS blends. (28th September 2016) - Kar, Goutam Prasanna; Biswas, Sourav; Bose, Suryasarathi
Abstract: A model immiscible blend system (PVDF/ABS, 50/50 wt/wt) was studied here and an attempt was made to stabilize the co-continuous structures using either a mutually soluble homopolymer (PMMA) or by introducing particles like graphene oxide sheets (GO) which preferentially localizes in PVDF or a combination of both i.e. PMMA wrapped GO, synthesized by in situ polymerization of MMA in presence of GO sheets (PMMA-GO). The improvement in structural properties couldn't be realized with GO alone or when added along with PMMA separately however, with PMMA-GO significant improvement in structural properties was realized. The coarsening of co-continuous microstructure during annealing was monitored here using both scanning electron microscopy and micro tomography. 2D SEM micrographs and the X-ray tomography reveal that the PVDF/ABS blends containing only PMMA coarsened upon annealing however, in presence of PMMA-GO although the phase dimension of the initial morphology was larger than the blends with only PMMA but the coarsening was suppressed as observed from micro-CT scans. The crystallization kinetics using modified Avrami model was assessed through non-isothermal DSC measurements to study the effect of PMMA, GO and PMMA-GO on the crystallization behaviour of the blends. Taken together, our results uncover an important observation wherein PMMA-GO effectively compatibilizes and stabilizes the morphology against post-processing operations like annealing in PVDF/ABS blends and also significantly improves the structural properties. Graphical abstract: Highlights: Various compatibilization routes like addition of a mutually soluble homopolymer (here PMMA); addition of nanosheets (here GO, graphene oxide), and PMMA wrapped GO were assessed here using a model blend system (PVDF/ABS). The improvement in structural properties couldn't be realized with GO alone or when added along with PMMA separately however, with PMMA-GO significant improvement in structural properties was realized. The coarsening of co-continuous microstructure during annealing was monitored using both scanning electron microscopy and X-ray microcomputed tomography. PMMA-GO effectively compatibilizes and stabilizes the morphology against post-processing operations like annealing in PVDF/ABS blends and also significantly improves the structural properties.